Liposuction Treatment of Lymphedema - Schaverien, Mark V.; Munnoch, D. Alex; Brorson, Håkan (Seminars in Plastic Surgery, 2018)
In the Western world, lymphedema most commonly occurs following treatment of cancer. Limb reductions have been reported utilizing various conservative therapies including manual lymph and pressure therapy, as well as by microsurgical reconstruction involving lymphovenous shunts and transplantation of lymph vessels or nodes. Failure of these conservative and surgical treatments to provide complete reduction in patients with long-standing pronounced lymphedema is due to the persistence of excess newly formed subcutaneous adipose tissue in response to slow or absent lymph flow, which is not removed in patients with chronic non-pitting lymphedema. Traditional surgical regimes utilizing bridging procedures, total excision with skin grafting, or reduction plasty seldom achieved acceptable cosmetic and functional results. Liposuction removes the hypertrophied adipose tissue and is a prerequisite to achieve complete reduction, and this reduction is maintained long-term through constant (24 h) use of compression garments postoperatively. This article describes the techniques and evidence basis for the use of liposuction for treatment of lymphedema.
Keywords: lymphedema; liposuction; adipose tissue; fat